Iberian ritual caves in the territory of Kelin (V-III bc) - Machause López, Sonia; Quixal Santos, David (Complutum, 2018)
The Requena-Utiel plateau, in the interior of the Province of Valencia, was within the territory of the city of Kelin during the Iberian Iron Age. One significant aspect of this territory is a high concentration of caves with Iberian materials. Cultural deposits in five of these caves are clearly the result of ritual practices inside. These ritual caves were spaces closely linked to the process of territorialization which occurred in the area between the 5th and 3rd centuries BC. In this article we reexamine those features, materials and associated chronologies, always integrating them with the nearby landscape and surroundings.